WASTEWATER MONITORING FOR WEST NILE VIRUS TRENDS IN KANSAS - Ghrist, McKenzie (My University, 2025)
Purpose and Scope: As part of my Applied Practice Experience at the Kansas Department of Health and Environment, this project explored the application of wastewater monitoring for West Nile Virus (WNV), a mosquito-borne virus with a high rate of asymptomatic infection. The goal was to assess whether wastewater data could enhance traditional surveillance methods and provide additional insight for public health professionals and evaluate the global implementation of similar approaches. Activities and Methods: My activities included statistical and spatial analyses using reported human WNV case data, wastewater monitoring data, serological data, and online mosquito search trends to explore wastewater monitoring for WNV from Kansas Department of Health and Environment. Autoregressive Integrated Moving Average models were used to model human WNV cases and assess utility of wastewater monitoring data, and Geographic Information System (GIS) tools were applied to visualize global incidence rate patterns and clustering. Findings: Wastewater WNV detection was moderately associated with reported human WNV cases at a five-month lag. The best model, which included wastewater, Google Trends, and immunoglobulin G testing data, outperformed models without the wastewater input. Spatial analysis showed regional clustering in North America and Europe, with mean centers near the Midwest and Mediterranean. A literature review identified over 25 countries exploring wastewater monitoring globally. Significance: These findings suggest wastewater monitoring supports WNV surveillance efforts in Kansas. Public health agencies should consider expanding wastewater-based monitoring, particularly in areas with underreported human cases. Continued research is needed to validate these findings over multiple seasons and inform policy decisions around integrated mosquito-borne disease monitoring.
Keywords: wastewater; West Nile Virus; Mosquito-borne Disease; Wastewater Monitoring; Wastewater-based Epidemiology; Arbovirus